1981
DOI: 10.1002/1097-0142(19810301)47:5<882::aid-cncr2820470512>3.0.co;2-e
|View full text |Cite
|
Sign up to set email alerts
|

Adjuvant immunotherapy of high risk stage I melanoma with transfer factor

Abstract: Following conventional surgical management, 100 patients with high risk Stage I melanoma were treated with transfer factor to reduce the incidence of disease recurrence. All patients had primary lesions invasive to Clark's level III or deeper and exceeding 1.0 mm in measured thickness. Ninety-six patients are available for analysis at 15 to 67 months (median: 30 months) after diagnosis. Nine patients have had a recurrence of disease (treatment failure), and one has died. Actuarial non-failure rate is 90%, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

1982
1982
1988
1988

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(3 citation statements)
references
References 31 publications
1
2
0
Order By: Relevance
“…On the other hand, the patients with stage I disease revealed a significant increase in 5-year survival (90%) compared to that (72%) of Knutson et a1 [4]. Interestingly, our 5-year disease-free results using an active specific form of adjuvant immunotherapy are similar (90%) to that of Blume et a1 [5] who used transfer factor as adjuvant immunotherapy for stage I disease (see Fig. 1).…”
Section: Discussionsupporting
confidence: 76%
“…On the other hand, the patients with stage I disease revealed a significant increase in 5-year survival (90%) compared to that (72%) of Knutson et a1 [4]. Interestingly, our 5-year disease-free results using an active specific form of adjuvant immunotherapy are similar (90%) to that of Blume et a1 [5] who used transfer factor as adjuvant immunotherapy for stage I disease (see Fig. 1).…”
Section: Discussionsupporting
confidence: 76%
“…The largest series evaluating transfer factor as an adjuvant agent was by Blume et a1 [120] and involved 100 patients with high-risk stage I melanoma (defined as Clark's Level 111-V and > 1.0 mm in thickness) followed for 30 months. Although the authors found an improvement in nonfailure rate (90 vs 63 %) and survival rate (99 vs 69%), the control group consisted of 46 contemporary but nonrandomized patients.…”
Section: Malignant Melanomamentioning
confidence: 92%
“…Our preliminary studies suggested that transfer factor might be effective as adjuvant therapy for melanoma patients,13 including those with surgically resectable lung metastases.14 Its adjuvant use also was supported by the favorable results of a nonrandomized, historically controlled trial of transfer factor in high-risk Stage I melanoma, reported by Blume and coworkers. 15 These considerations led us to undertake a randomized, double-blind, placebo-controlled trial of TF as adjuvant therapy in malignant melanoma treated surgically.…”
mentioning
confidence: 99%